Automatic Testing System for Performance Parameters of Viscoelastic Materials - Du, Yibing; Wang, Pengyu; Liang, Rongting; Zhou, Xinju; Chen, Siyu (International Journal of Computer Science and Information Technology, 2024)
With the development of science and technology, viscoelastic materials such as metals and polymers are widely used in various engineering fields and structural design in China, and the creep aging forming technology and time-stressed relaxation forming technology developed by creep and stress relaxation theory has been widely used in the aviation industry. Creep and stress relaxation experiments are carried out on materials under different loading conditions, and the testing machine unit is used to realize the automatic control of the whole process of the experiment and the storage of experimental data.